Municipal Power. The Territorialization Process of the Chilean Central Government, 1830-1890 (Palimpsesto, 2020)
This article offers an empirical study of the process of territorial anchoring of the Chilean State during the 19th century, taking into account the forms of articulation between the central government and the municipalities. The main question is how state power has been locally built. The answer argues that the municipality was a political space that articulated at the local level the exercise of this power, institutionalizing at the same time as establishing a modern conception of it. From this perspective, the process of state construction is resized locally by the analysis of another form of power distinguishable from the central apparatus. In doing so, it allows to recover the protagonism of the municipalities as other centers of power that dynamize the processes of institutionalization and territorial concretion of the government, and discuss the monocentric interpretation of the Chilean State that has reproduced the myth of a historical municipal weakness.
Keywords: municipalities; local power; central government; State-Building